The onset of mucormycosis amidst COVID-19 crises in India: A systematic analysis - Shakti Rath (Wolters Kluwer -Medknow Publications, 2022)
A descriptive analysis of the "Mucormycosis" or "black fungus infection" surge in India is given in this article. Amidst the pool of deadly COVID-19 crises and when India is suffering its second wave, another dangerous but rare fungal infection of mucormycosis is rising. This study analyses the occurrence and prevalence of black fungus infection between India and other countries with a higher or similar COVID-19 infection peak. This study also identifies that mucormycosis is a more significant problem in India than in any other country.